Satellite data archives reveal positive effects of peatland restoration: albedo and temperature begin to resemble those of intact peatlands - Iuliia Burdun; Mari Myllymäki; Rebekka R E Artz; Mélina Guêné-Nanchen; Leonas Jarašius; Ain Kull; Erik A Lilleskov; Kevin McCullough; Mara Pakalne; Jiabin Pu; Jūratė Sendžikaitė; Liga Strazdina; et al. (Environmental Research Letters, 2025)
Peatlands store significant amounts of carbon, which is released as greenhouse gases when peatlands are degraded. Restoration and rewetting can help prevent these emissions, while continuous monitoring is critical for evaluating their success. Using satellite-derived observations of essential climate variables, we conducted the first large-scale assessment of how peatland restoration influences land surface temperature (LST), albedo, and vegetation across 72 sites in North America and Europe. Our findings indicated that before restoration, degraded peatlands had a commonly lower daytime LST and albedo but higher nighttime LST, leaf area index (LAI), and fraction of absorbed photosynthetically active radiation (FPAR) compared to intact sites. The largest restoration-induced absolute values of monthly changes reached +3.18 °C (daytime LST), −1.22 °C (nighttime LST), −2.54 (LAI), −0.29 (FPAR), and −0.16 (albedo). While restored peatlands tended to align more closely with intact sites a decade after restoration began, the probability of this alignment varied depending on the climate variables. Restored peatlands became more similar than different to intact sites in nighttime LST and albedo after a post-restoration decade, with high similarity projected within five decades. Peatland restoration modifies local and regional climate and should be included in future climate projections.